Low-Temperature Reverse Microemulsion Synthesis, Characterization, and Photocatalytic Performance of Nanocrystalline Titanium Dioxide - Zhang Liu; Zicong Jian; Jianzhang Fang; Xiaoxin Xu; Ximiao Zhu; Shuxing Wu (International Journal of Photoenergy)
Nanocrystalline titanium dioxide (TiO2) was synthesized in microemulsions by using cetyltrimethylammonium bromide (CTAB) as surfactant. In order to investigate the crystal transformation and photoactivity at low temperature, the as-prepared precipitates were aged at 65°C or calcined at various temperatures. Analyses using powder X-ray diffraction (XRD) and Fourier transform infrared microscopy (FT-IR) showed that precursors without aging or calcination were noncrystal and adsorbed by surfactant. After aging for 6 h, the amorphous TiO2 began to change into anatase. The obtained catalysts, which were synthesized in microemulsions with weight ratios of n-hexanol/CTAB/water as 6 : 3 : 1 and calcined at 500°C, presented the highest photocatalytic degradation rate on methyl orange (MO), while the catalysts, which were aged at 65°C for 90 h, also exhibited an outstanding photocatalytic performance and a little higher than that of the commercial titania photocatalyst Degussa P25.